The virtual team managing culture and technology - Toll, E. Erich; Taylor, Jess (USA : Bigworldmedia)
Discussed about business via internet and wireless technology
Editor, John Vanderpoel
Narrator : Lee Mas
Keywords: Teams in the workplace -- Computer networks; Business enterprises -- Computer networks